2007
DOI: 10.1111/j.1460-9568.2007.05830.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of synaptic transmission and nociceptive behaviour in HPC‐1/syntaxin 1A knockout mice following peripheral nerve injury

Abstract: Our previous analysis of HPC-1/syntaxin 1A knockout (KO) mice indicated that HPC-1/syntaxin 1A plays an important role in the synaptic plasticity of the hippocampus in vitro and learning behaviour in vivo. In order to gain further insights into the physiological functions of HPC-1/syntaxin 1A, we studied the changes in the plasticity of synaptic transmission in the superficial dorsal horn of the spinal cord following a peripheral nerve injury in HPC-1/syntaxin 1A KO and wild-type (WT) mice. The von Frey filame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
(98 reference statements)
1
9
0
Order By: Relevance
“…In fact, we showed alterations in proteins implicated in synapse and axonal transport, such as a decrease in syntaxin‐1 protein levels. It is known that this protein plays an important role in learning behavior in vivo (Takasusuki et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we showed alterations in proteins implicated in synapse and axonal transport, such as a decrease in syntaxin‐1 protein levels. It is known that this protein plays an important role in learning behavior in vivo (Takasusuki et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we showed alterations in proteins implicated in synapse and axonal transport, such as a decrease in syntaxin-1 protein levels. It is known that this protein plays an important role in learning behavior in vivo (Takasusuki et al, 2007). Indeed, the formation of long-term potentiation is associated with an increase in levels of syntaxin-1 that occur with the augment of depolarization-induced glutamate release, which in turn leads to the propagation of synaptic plasticity (Helme-Guizon et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…1C, the ASR was also significantly enhanced in STX1A −/− mice, suggesting hypersensitivity to auditory stimuli. We recently reported that STX1A −/− mice showed enhanced allodynia and hypersensitivity to painful stimuli (Takasusuki et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Presynaptic functional changes after peripheral nerve injury that increase synaptic strength include alterations in the synthesis of transmitters and neuromodulators (Obata et al 2003) and in calcium channel density (Hendrich et al 2008, Li et al 2004). Postsynaptic changes involve phosphorylation of N-methyl-D-aspartate (NMDA) subunits (Ultenius et al 2006) and increased receptor density due to trafficking and enhanced synthesis of ion channels and scaffold proteins (Cheng et al 2008, Iwata et al 2007, Miyabe et al 2006, Takasusuki et al 2007, Tao et al 2003). Drugs that attenuate central sensitization by acting on calcium channel subunits to decrease transmitter release and on NMDA channels to reduce transmitter action (Chizh et al 2007; Jorum et al 2003) are effective treatment options in neuropathic pain (Dworkin et al 2007).…”
Section: Mechanisms Of Neuropathic Painmentioning
confidence: 99%